Perceptions of intelligent building in Malaysia : case study of Kuala Lumpur / Omar Jamaludin - Jamaludin, Omar (2011)
Intelligent Building (IB) is the term used to describe new office buildings in Kuala Lumpur, Malaysia. While the government is introducing the Multimedia Super Corridor through the governments' 2020 Vision, the perceptions of IB are fully exploited to promote the ICT and technological development as well as the economic regeneration of the country. Eventually, without a comprehensive understanding on IB, various interpretations in technological idioms are generating throughout the progress of the development of the new office buildings in Kuala Lumpur as the majority of the people are overwhelmed with the high technological concept of IB and the popularity achievements of the government on technological uptakes at local and international level. This research analysed the perceptions of IB in Malaysia by investigating different interpretations on IB among the people in Kuala Lumpur in the attempt to explore how the various perceptions influenced the development of IB. In addition to that, a better understanding on IB is acquired from the experts' point of view and government document are critically analysed to investigate the local and federal government agenda on IB development. The existing model of IB is validated by exploring the perceptions of people working in the office buildings that have been referred as IB by the majority of the people in Kuala Lumpur. The research also analysed how do the perceptions regarding IB compared across the stakeholders before outlining recommendations to strengthen the definition of IB, the assessment criteria and practical practices to further assist on the development of IB in Kuala Lumpur. Questionnaire survey, content analysis and non structured interview are employed as the methodology of the research.